Comparison of the expression levels of TNF-Î±, IL-6, hsCRP and sICAM-1 inflammatory factors, bone mineral density and nutritional status between diabetic and normal pregnant women - Wang, Qian; Wang, Chun (Cellular and Molecular Biology, 2020)
To compare the ultrasound bone mineral density, nutritional status and inflammatory state of pregnant women with gestational diabetes mellitus (GDM) and those with normal blood glucose. Retrospective analysis of pregnant women who were prenatally examined and delivered in The 5th People's Hospital of Ji'nan from May 2015 to July 2017 was performed, including 68 subjects with normal blood glucose in the control group and 74 subjects with GDM in the experiment group. The bone mineral density, nutritional status and inflammatory state were measured by enzyme-linked immune sorbent assay (ELISA). The bone mineral density of pregnant women with GDM was lower than that of the control group; the incidence of osteoporosis in GDM pregnant women was higher than that in the control group. The energy intake of GDM pregnant women was high, and the usage rate of fruits, sweets, deep-fried products and night snack was higher than that of normal pregnant women. The expression levels of TNF-Î±, IL-6, hsCRP and sICAM-1 inflammatory factors in GDM pregnant women were significantly higher than those with normal blood glucose. The bone mineral density of pregnant women with GDM is lower than that with normal blood glucose. Therefore, the prevention of GDM in pregnant women is also important for their bone health. GDM pregnant women's health education should be strengthened and reasonable dietary interventions should be carried out as soon as possible. TNF-a, IL-6, hsCRP, and sICAM-1 may be involved in the inflammatory process of GDM.